DIAGENESIS EFFECTS ON SPECIFIC CARBON ISOTOPE COMPOSITION OF PLANT N-ALKANES - Nguyen Tu T.T.; Bardoux G.; Mariotti A.; Derenne S.; Largeau C. (My University, 2004)
The stable carbon isotope compositions of individual n-alkanes extracted from leaves of (1) Ginkgo biloba degrading in a well-drained soil and (2) Eretmophyllum, a fossil Ginkgoale, were investigated in a first approach to refining the estimate of potential diagenetic effects on the isotopic composition of sedimentary alkanes derived from higher plants; n-alkanes extracted from fresh leaves of G. biloba appeared 13C-depleted when compared with bulk leaves. Within a given extract they exhibited characteristic variability in specific isotope composition with respect to chain length. Although the isotope composition of bulk leaves remained unchanged through senescence and litter formation, the specific n-alkane isotopic composition varied in two respects: (i) general 13C-enrichment in all n-alkanes and (ii) homogenisation of specific isotopic composition of all the n-alkanes of a given extract. As for fresh and degrading leaves of G. biloba, n-alkanes extracted from the fossil Eretmophyllum appeared 13C-depleted when compared with bulk leaves. Their isotope distribution patterns suggested that the isotope composition of fossil alkanes may have been slightly affected by diagenesis. Results for degrading leaves and fossil leaves (1) indicated that the isotope composition of individual alkanes can be more affected by degradation than that of bulk leaves and (2) confirmed that the isotope signal in fossils, and sedimentary organic matter in general, may be less altered than in the organic matter of well-drained soil.